Numerical modeling of RC hollow piers with a damage model - Pedro Delgado (2008)
This paper reports on the numerical modeling of some RC hollow section piers experimentally tested under cyclic conditions. Bearing in mind that hollow sections piers exhibit a structural behavior quite similar to that of a structural wall, recourse is made to a refined modeling strategy where the concrete in compression and tension is simulated using 3D solid finite elements with a continuum damage mechanics model and truss elements with the Menegotto-Pinto model for the cyclic behavior of the steel reinforcement. The numerical simulations encompass bending dominated piers and also shear controlled cases, all of them experimentally tested. In addition, two different transverse reinforcement arrangements are studied, one representative of several existing bridge piers without seismic design provisions and another in accordance with new Eurocode requirements. Comparison of numerical results with the corresponding experimental ones has provided evidence on the modeling adequacy to simulate the pier response, both bending and shear dominated, and allowed also to confirm the improvement of cyclic response capacity of EC8 designed piers when compared with existing traditional ones.